1999
DOI: 10.1021/ma981865o
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Structure of pH Dependent Polyelectrolyte Block Copolymer Micelles

Abstract: We use fluorescence spectroscopy, dynamic light scattering (DLS), and small-angle neutron scattering (SANS) to characterize the structure of 2-(dimethylamino)ethyl methacrylate/2-(diethylamino)ethyl methacrylate (DMAEMA/DEAEMA) block copolymer micelles. The copolymers exhibit a strong pH dependence, where protonation of the tertiary amines along the side chains cause the blocks to be soluble in water. Fluorescence results show a critical degree of protonation below which single chains aggregate to form micelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
261
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(277 citation statements)
references
References 21 publications
14
261
1
1
Order By: Relevance
“…These measurements reveal the presence of micellar aggregates due to the hydrophobicity of the pendant diclofenac and hydrophilicity of the PGA backbone. The difference in size depending on solution conditions is likely a consequence of the lower ionization and increased charge shielding occurring in 100 mM sodium acetate, pH 6.3 compared with 10 mM sodium phosphate, pH 7.4; the reduced electrostatic repulsion in the former allows for higher aggregation numbers and thus larger particle sizes (44). Because of the self-assembly into micellar aggregates, pendant ester linkages are sequestered into the hydrophobic core, which is likely a major factor in the slow diclofenac release kinetics that we observed.…”
Section: Resultsmentioning
confidence: 99%
“…These measurements reveal the presence of micellar aggregates due to the hydrophobicity of the pendant diclofenac and hydrophilicity of the PGA backbone. The difference in size depending on solution conditions is likely a consequence of the lower ionization and increased charge shielding occurring in 100 mM sodium acetate, pH 6.3 compared with 10 mM sodium phosphate, pH 7.4; the reduced electrostatic repulsion in the former allows for higher aggregation numbers and thus larger particle sizes (44). Because of the self-assembly into micellar aggregates, pendant ester linkages are sequestered into the hydrophobic core, which is likely a major factor in the slow diclofenac release kinetics that we observed.…”
Section: Resultsmentioning
confidence: 99%
“…This weakly basic copolymer is molecularly dispersed at low pH, but forms well-defined PDEA-core micelles in alkaline solution. [20] The unimer-to-micelle transition occurs over a relatively narrow range (pH 7-9), which depends on both the molecular weight and block composition of the copolymer. Bütün et al showed that the PDMA blocks of these copolymers can be selectively quaternized by reaction with simple alkyl halides to produce permanently cationic blocks.…”
mentioning
confidence: 99%
“…Polyamines with appropriate hydrophobicity, including poly[2-(N,N-diethylamino)ethyl methacrylate] (PEAMA), are known to show phase transitions as a function of pH [25][26][27]. Utilizing this character, various environmentally sensitive polymeric materials have been developed.…”
Section: Ph Response Of Hanpmentioning
confidence: 99%